2008
DOI: 10.1002/ajmg.b.30839
|View full text |Cite
|
Sign up to set email alerts
|

Linkage studies in familial idiopathic basal ganglia calcification: Separating the wheat from the chaff

Abstract: Idiopathic Basal Ganglia Calcification (IBGC) is a neuropsychiatric condition characterized by brain calcinosis, heterogeneous motor impairment and behavioral symptoms. The IBGC1 locus was the first region linked to this phenotype in an American family, but another kindred from Spain was also reported as possibly associated with this locus. Our group excluded this locus in additional families together with an independent study of an Australian pedigree with IBGC, but without clinical symptoms. Recently, a larg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The nosology of this disorder needs more debate in order to establish standard diagnostic criteria necessary for the identification of loci or mutation responsible for FIBGC (Oliveira and Lemos 2009;. However, given the detailed radiological basis by which BGC was determined and the absence of secondary symptoms, while we cannot rule out that our family represents a novel syndrome, it most certainly resembles more FIBGC than other syndromes such as autosomal dominant chromosome instability syndrome (Ishikawa et al 2000).…”
Section: Discussionmentioning
confidence: 96%
“…The nosology of this disorder needs more debate in order to establish standard diagnostic criteria necessary for the identification of loci or mutation responsible for FIBGC (Oliveira and Lemos 2009;. However, given the detailed radiological basis by which BGC was determined and the absence of secondary symptoms, while we cannot rule out that our family represents a novel syndrome, it most certainly resembles more FIBGC than other syndromes such as autosomal dominant chromosome instability syndrome (Ishikawa et al 2000).…”
Section: Discussionmentioning
confidence: 96%
“…The disease is classified by intracranial calcification of the basal ganglia with the globus pallidus region being particularly affected (1,2). FD is frequently familial and thought to have autosomal dominant inheritance linked to chromosome 14q (4)(5)(6)(7). FD is frequently familial and thought to have autosomal dominant inheritance linked to chromosome 14q (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Several other families have been described more recently, and the list grows together with the ramping up of availability of neuroimaging procedures worldwide and with careful screening of patient's relatives [2][3][4][5][6][7].…”
mentioning
confidence: 99%
“…Kobari et al (1997) reported a 48-year-old man with intellectual decline, Parkinsonism and mild cerebellar ataxia [5]. Kobari et al (1997) reported a 48-year-old man with intellectual decline, Parkinsonism and mild cerebellar ataxia [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation